Nélida E. Donni De Mirande, Susana H. Boretti De Macchia, María Cristina Ferrer De Gregoret, Carmen Sánchez Lanza, Nora Martino. El español de Rosario: estudios sociolingüísticos. - Montes Giraldo, José Joaquín (Thesavrvs, 2022)
Reseña de libros.